Congenital double upper lip: A case report and review of the literature - John Spencer M. Daniels (Elsevier, 2010)
Congenital double lip is a rare developmental anomaly which usually involves the upper lip more than the lower lip. It may occur in isolation or as a part of Ascher's syndrome. Sometimes upper and lower double lips occur simultaneously.The occurrence of double lip may result in facial deformity especially when the patient attempts to talk, smile or even show the teeth. It may also interfere with speech or mastication. Although surgery may be undertaken to facilitate speech and mastication, the majority of cases are operated for cosmetic reasons.A case of congenital double upper lip, which was surgically treated after orthodontic treatment, for cosmetic reasons, is reported. The different surgical approaches to the management of double upper lip are reviewed with a note on timing of surgery in patients who have concurrent orthodontic or prosthodontic problems.Although the majority of cases of double lip are treated by Plastic Surgeons and Oral and Maxillofacial Surgeons, it is important to make dentists aware of this condition since they may be the first clinicians to encounter patients with this abnormality. Keywords: Double lip, Congenital, Acquired, Ascher's syndrome, Ellipse excision, W-plasty, Central constriction, Mucous gland hyperplasia, Pars villosa, Pars glabrosa